Behavioral Biases, Financial Literacy, and Female Investors: The Role of Social Media - Vera Setyadi; Indarto Indarto; Dian Indriana (MATRIK: JURNAL MANAJEMEN, STRATEGI BISNIS, DAN KEWIRAUSAHAAN, 2025)
The Indonesian capital market faces challenges in investor growth, particularly with low investment levels among women. Female investors lag behind men in both the number of investors and the value of investments. Despite an increase in the number of female investors, their investment values remain low, indicating limited active participation. This research aims to examine how financial literacy and behavioral biases influence Indonesian female investors decisions, with social media as a moderating variable. Using a sample of 126 female investors, the test was conducted with PLS-SEM. The results showed that regret aversion bias significantly negatively impacts female investors decisions, while financial literacy has a positive and significant effect. Overconfidence bias and herding behavior do not significantly influence investment decisions. Social media does not moderate the effects of these biases and financial literacy on investment decisions but could act as predictor moderation variable with significant positive impact on investment decisions.